The effectiveness of expressive writing on students’ subjective well-being - Angeline Widjaja; Dinda Khairunnisa Nabila; Nadia Carissa; Theresia Yosephine Anggristiany; Putri Amanda Salwa; Setiasih Setiasih (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTWriting can serve as a means for individuals to express their feelings or internal meanings. This study aims to determine whether there the expressive writing has an impact on the subjective wellbeing of students. This study employed a true experimental design using the Pretest Post-test Control Group Design. The participants consisted of 22 new students from the 2023 academic year, selected using convenience sampling techniques. Data were collected the Oxford Happiness Questionnaire (OHQ) and analyzed using the Independent Sample T-Test. The results of the data analysis indicated no significant different in subjective-well being scores between the experimental group (EG) and the control group (CG) (p = 0.700, p > 0.05)). This suggests that expressive writing does not influence the subjective well-being of students. The implementation of the intervention (expressive writing) was carried out when students were taking final semester exams which potentially disrupts their concentration and focus, hindering their ability to fully express their feelings or experiences in writing. Therefore, to ensure the effectiveness of the intervention, it is important to consider the participants’ conditions.ABSTRACTMenulis dapat menjadi sarana untuk mengekspresikan perasaan atau makna yang ada pada dirinya individu. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh expressive writing terhadap kesejahteraan subjektif mahasiswa. Penelitian ini merupakan penelitian eksperimen murni (true experiment) dengan desain Pretest Post-test Control Group Design. Partisipan penelitian ini adalah mahasiswa baru angkatan 2023, sebanyak 22 orang, diperoleh dengan teknik convenience sampling. Pengumpulan data menggunakan Oxford Happiness Questionnaire (OHQ). Data yang diperoleh kemudian dianalisis dengan Independent Sample T-Test. Hasil analisis data menunjukkan tidak terdapat perbedaan yang signifikan skor SWB antara kelompok eksperimen (KE) dan kelompok kontrol (KK) (p= 0,700, p > 0,05). Hal tersebut menunjukkan bahwa expressive writing tidak berpengaruh terhadap kesejahteraan subjektif mahasiswa. Pelaksanaan intervensi expressive writing yang dilakukan di saat mahasiswa menjalani ujian akhir semester membuat konsentrasi partisipan terganggu dan kurang fokus dalam menuliskan apa yang dirasakan atau dialaminya. Oleh karena itu agar hasil intervensi berpengaruh perlu diperhatikan kondisi partisipannya.